Study of the VMM1 read-out chip in a neutron irradiation environment. (20th May 2016) - Alexopoulos, T.; Fanourakis, G.; Geralis, T.; Kokkoris, M.; Kourkoumeli-Charalampidi, A.; Papageorgiou, K.; Tsipolitis, G.
Abstract: Within 2015, the LHC operated close to the design energy of √ s = 13–14 TeV delivering instantaneous luminosities up to ℒ = 5 × 10 33 cm −2 s −1 . The ATLAS Phase-I upgrade in 2018/19 will introduce the MicroMEGAS detectors in the area of the small wheel at the end caps. Accompanying new electronics are designed and built such as the VMM front end ASIC, which provides energy, timing and triggering information and allows fast data read-out. The first VMM version (VMM1) has been widely produced and tested in various test beams, whilst the second version (VMM2) is currently being tested. This paper focuses on the VMM1 single event upset studies and more specifically on the response of the configuration registers under harsh radiation environments. Similar conditions are expected at Run III with ℒ = 2 × 10 34 cm −2 s −1 and a mean of 55 interactions per bunch crossing. Two VMM1s were exposed in a neutron irradiation environment using the TANDEM Van Der Graaff accelerator at NSCR Demokritos, Athens, Greece. The results showed a rate of SEU occurrences at a measured cross section of (4.1±0.8)×10 −14 cm 2 /bit for each VMM. Consequently, when extrapolating this value to the luminosity expected in Run III, the occurrence is roughly 6 SEUs/min in all the read-out system comprising 40, 000 VMMs installed during the Phase-I upgrade.